An investigation of the isolation, characterisation and application of hydantoinases for the industrial production of amino acids - Kirchmann, Shaun (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
This thesis describes a series of investigations into the hydantoin-hydrolysing activity of bacterial strains RU-KM1 and RU-OR, which were previously isolated for their ability to hydrolyse hydantoins to amino acids. The main aim of the study was to develop biotransformations with potential application in the production of enantiomerically pure amino acids using a bioreactor based system utilising the hydantoin hydrolysing enzymes of the two isolated microorganisms. Different substituted hydantoins may be used as substrates by these enzymes for the production of a variety of amino acids. These are not only important for amino acid production, but they may be used for production of other industrially important compounds, such as semisynthetic penicillin/ampicillin, L-aspartame (sweetener), Fluvalinate (insecticide), Enalapril (ACE inhibitor). Thus, the ability of the above-mentioned strains to hydrolyse these substrates was investigated, with the view to utilizing the maximum potential of these biocatalysts. Hydantoin conversion involves a two-step hydrolysis reaction which yields, initially, an N-carbamylamino acid intermediate, and subsequently, an amino acid. The hydantoin-hydrolysing enzymes of a Pseudomonas sp. RU-KM1, and an Agrobacterium sp. RU-OR were characterised as whole cells and in a crude extract preparation, and reaction conditions for its biocatalytic application were optimised. The optimum conditions for conversion of hydantoin to glycine were found to be 1 hour at 40 °C, with conversion yields greater than 30 % achieved. The enzymes of RU-KM1 demonstrated considerable stability, retaining 80 % of their activity after storage for 2 weeks at 4 °C. The activities of the enzymes were increased by the addition of a detergent to the extraction medium, suggesting that the enzymes might be membrane-bound. The results of the determination of the metal-dependence of the hydantoinase and N-carbamoylase of RU-KM1 suggested that these enzymes required metal ions for activity, with metal ions such as Cu[superscript (2+)], Fe[superscript (2+)], and Co[superscript (2+)] resulting in no significant change in enzyme activity, however there was an activation of the enzymes when Mn[superscript (2+)] was added to the enzymes. The stereoselectivity of the enzymes was investigated, and the results suggested that the hydantoinase was D-selective, whereas the N-carbamoylase was shown to be L-selective by other researchers. The hydantoin substrate selectivity of RU-KM1 and RU-OR was investigated, and the organisms were shown to be able to hydrolyse all of the seven substrates tested. However, there was a difference in activity levels between crude extract preparations and whole cells, with crude extracts generally showing slightly lower activity than whole cells in RU-KM1, and the whole cells or RU-OR showing the lower activity than its crude extract. Some difference was also observed in the order of preference of substrates between whole cells and crude extracts. The preferred substrate for RU-KM1 whole cells was isopropylhydantoin, whereas the crude extract preparation preferentially hydrolysed p-hydroxyphenylhydantoin, achieving 57 % and 52 % conversions respectively. RU-OR whole cells preferred methylhydantoin where as the crude extract preferred isopropylhydantoin, and showed 49 % and 51 % conversions respectively. The enzymes were characterised in terms of their temperature and pH optima, inducer requirements, and product inhibition studies. The hydantoinase of RU-KM1 was shown to be inducible with low levels of hydantoin, and thermostable upto 75 °C with its optima between 60 and 70 °C. The N-carbamoylase was shown to have its optima at 50 °C. The addition of ATP (0.5 mM), DTT (1 mM) and a protease inhibitor (2 mg.mL[superscript (-1)]) all increased the hydantoinase activity of RU-KM1 crude extract, however they had very little effect on the N-carbamoylase activity. The hydantoinase enzyme from extracts of RU-KM1 was partially purified by development of cell disruption methods using mechanical and lysing enzymes, followed by precipitation and chromatographic resolution. The results obtained showed a hydantoinase enzyme of between 48 and 66 kDa. RU-KM1 was grown under fermentation conditions using different minimal media. The activity and yields under these conditions were low. Previous attempt to grow the organism in a rich medium had resulted in an increase in biomass but no hydantoinase activity. A rich medium was developed by carbon and nitrogen optimisation and yielded biomass up to 30 g.L[superscript (-1)] dry cell weight. The hydantoinase activity was restored by nitrogen starvation in stationary phase. This resulted in high biomass with increased activity. This data is currently in press. Crude extract and whole cells were immobilised on flat sheet membranes, hollow fibre membranes and in alginate beads. Low hydantoinase activity was measured in bioreactors using membranes in different configurations. A significant increase in hydantoinase activity was measured when the crude extract was immobilised in sodium alginate, as a result of stabilisation of the N-carbamoylase. Temperature and pH optima were unaffected by the immobilisation procedure, however the durability of the enzymes increased 2-fold. Different configurations of the bioreactor were investigated, as well as a hydroxyphenylhydantoin as an alternative substrate in this study. The bioreactors showed a near 95 % conversion of the hydantoin to glycine, and a 99 % conversion using HPG. In conclusion, the hydantoin-hydrolysing enzymes of RU-KM1 have been shown to be possibly membrane associated, which is a novel finding. This study has shown that the hydantoinase of RU-KM1 is D-stereoselective, with high temperature stability. A growth medium was developed for the rapid production of active biomass. A bioreactor was developed using a single and a dual biocatalyst configuration, which was capable of hydrolysing hydantoin and monosubstituted hydantoins to produce amino acids. To our knowledge this system is the first such dual biocatalyst system reported for the production of amino acids.
Keywords: Hydantoin; Amino acids; Hydrolysis